2022
DOI: 10.1097/md.0000000000030643
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of m6A regulators and the nomogram construction in glioma patients

Abstract: Although N6-methyladenosine (m6A) has been implicated in various biological functions in human cancers, its role in predicting the prognosis of glioma remains unclear. In this study, the transcriptome expression profiles and the clinical data of 961 patients were derived from the Chinese Glioma Genome Atlas (CGGA). We comprehensively evaluated the association between the expression of m6A regulators and the prognosis of glioma and established a 3-gene (YTHDF2, FTO, and ALKBH5) risk signature using least absolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We compared our model with several other prognostic models to assess the importance of the PANoptotic score for predicting the prognosis of glioma. The results showed that the prediction accuracy of our model was better than other models that have been reported (Chen et al, 2021;Liu P. et al 2022;Zeng et al, 2022) (Figures 5D-F and Supplementary Figures S5A-F).…”
Section: Development and Validation Of A Panoptotic Score Model Based...mentioning
confidence: 55%
See 1 more Smart Citation
“…We compared our model with several other prognostic models to assess the importance of the PANoptotic score for predicting the prognosis of glioma. The results showed that the prediction accuracy of our model was better than other models that have been reported (Chen et al, 2021;Liu P. et al 2022;Zeng et al, 2022) (Figures 5D-F and Supplementary Figures S5A-F).…”
Section: Development and Validation Of A Panoptotic Score Model Based...mentioning
confidence: 55%
“…In previous studies, transcriptomics-based prognostic models for glioma have also been proposed. For example, Chen et al constructed a prognostic model of glioblastoma based on the function of STEAP (Six-transmembrane epithelial antigen of the prostate) family, STEAP2-and STEAP3-based prognostic risk score ( Chen et al, 2021 ); Zeng et al researched a prognostic model of glioma based on pyroptosis named pyroptosis-related risk signature (PRRS) ( Zeng et al, 2022 ); Liu P. et al (2022) proposed a prognostic model of glioma based on m6A regulators model called risk score, etc. The predictive performance of our constructed model was better than each of the above models by comparison of area under the ROC curve (AUC).…”
Section: Discussionmentioning
confidence: 99%
“…In other tumor studies, it was found that m6A in peripheral blood of patients with gastric cancer increased with the progression and metastasis of gastric cancer, but decreased signi cantly after surgery, suggesting that m6A level in peripheral blood is a promising noninvasive diagnostic biomarker for gastric cancer patients [22]. In the study of m6A RNA methylation in glioma, it was found that high expression of m6A was associated with poor prognosis and tumor grade [23]. In the study of urological malignancies, high levels of m6A RNA methylation in mRNA were found to promote prostate cancer progression by regulating subcellular protein localization, and patients with high m6A RNA methylation had poor survival bene ts [24].…”
Section: Discussionmentioning
confidence: 99%
“…FTO’s influence extends to mitochondrial functions, affecting the expression of genes like SDHA and regulating the STAT3/FTO axis [ 138 ]. Prognostic studies suggest that FTO can predict poor outcomes in glioma patients, and inhibitors targeting FTO have shown promise in reducing tumorigenicity and aggressiveness in glioma models [ 139 , 140 , 141 , 142 ]. FTO expression is also linked to the decreased apoptosis and increased proliferation of glioma cells [ 143 ], and its inhibition suppresses GSC growth and self-renewal [ 112 ].…”
Section: Rna Modifications In Gliomamentioning
confidence: 99%